Sistem Informasi Website Company Profile Pada Dinas Koperasi dan UKM Kabupaten Pali - Handoko, Handoko; Dhamayanti, Dhamayanti; Marcelina, Dona (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
The Company Profile Website Information System has become an increasingly important means of introducing organizations to the broader community. Effective and efficient exposure is crucial for promoting related services, programs, and information in the Department of Cooperatives and Small and Medium Enterprises (UKM) in Pali Regency. This research shows that the prototype method can be applied to develop a company profile by utilizing HTML, PHP, JavaScript, and MySQL programming languages. This system can provide accurate and up-to-date information to the public and increase awareness about the services offered by the Department of Cooperatives and SMEs in Pali Regency. This research contributes to the application of information technology in the government and public service sectors, especially in strengthening the image of organizations through modern digital expressions.